Small producer participation in export vegetable supply chains and poverty: Evidence from different export schemes in Tanzania - Marwan Benali; Bernhard Brümmer; Victor Afari-Sefa (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2017)
With the rise and consolidation of modern supply chains, literature has put emphasis on the welfare effects for participating small producers but has often considered these effects through the comparison of participating producers with those not participating at all. Using an endogenous switching regression model, we assess in this paper the effects of small producer participation in export vegetable supply chains in Tanzania on household income and compare the effects of supplying two different types of French beans and snap peas export supply chains, defined as high-value (HVESC) and regular export supply chains (RESC), respectively. We find that participation in export supply chains increases producers' household per capita income. We also find evidence that these effects may vary from one type of export supply chains to the other and are mainly driven by HVESC, which confirms that participation in export supply chains may have varying effects depending on individual circumstances and participation conditions. We also disaggregate the analysis with respect to the producers' farm size and income level and find evidence that richer and larger producers benefit from supplying the HVESC while supplying the RESC can increase the household per capita income of some poorer producers.
Keywords: C24; O12; O13; Q12; Q13; 330; small producers; export supply chains; horticulture; endogenous switching regression; household income; Tanzania